2023
DOI: 10.1007/s00294-023-01269-z
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal effect induced by itraconazole in Candida parapsilosis largely depends on the oxidative stress generated at the mitochondria

Abstract: In Candida parapsilosis, homozygous disruption of the two genes encoding trehalase activity increased the susceptibility to Itraconazole compared with the isogenic parental strain. The fungicidal effect of this azole can largely be counteracted by preincubating growing cells with rotenone and the protonophore 2,4-Dinitrophenol. In turn, measurement of endogenous reactive oxygen species formation by flow cytometry confirmed that Itraconazole clearly induced an internal oxidative stress, which can be significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Evidence of ROS formation in response to azole exposure has been reported in both yeasts and molds ( Table 1 ). Interestingly, in Candida , the most robust and reproducible evidence for ROS formation has been obtained in response to fungicidal azoles: miconazole and itraconazole ( Kobayashi et al., 2002 ; Francois et al., 2006 ; Belenky et al., 2013 ; Lee and Lee, 2018 ; Muñoz-Megías et al., 2023 ). In contrast, investigating whether C. albicans induces ROS in response to fluconazole, which is fungistatic in Candida , has produced conflicting results ( Kobayashi et al., 2002 ; Francois et al., 2006 ; Belenky et al., 2013 ) ( Table 1 ).…”
Section: Ros Form In Fungi During Antifungal Drug Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of ROS formation in response to azole exposure has been reported in both yeasts and molds ( Table 1 ). Interestingly, in Candida , the most robust and reproducible evidence for ROS formation has been obtained in response to fungicidal azoles: miconazole and itraconazole ( Kobayashi et al., 2002 ; Francois et al., 2006 ; Belenky et al., 2013 ; Lee and Lee, 2018 ; Muñoz-Megías et al., 2023 ). In contrast, investigating whether C. albicans induces ROS in response to fluconazole, which is fungistatic in Candida , has produced conflicting results ( Kobayashi et al., 2002 ; Francois et al., 2006 ; Belenky et al., 2013 ) ( Table 1 ).…”
Section: Ros Form In Fungi During Antifungal Drug Exposurementioning
confidence: 99%
“…Additionally, the same study reported that although the echinocandin caspofungin also elicited robust ROS induction (at least as high as amphotericin B), no mitochondrial membrane peroxidation was observed during caspofungin treatment (lipid peroxidation and Yap1 localization were not reported for caspofungin) ( Shekhova et al., 2017 ). Furthermore, although in C. parapsilosis itraconazole induced ROS production, there was no concomitant increase in the activities of either catalase or superoxide dismutase, two of the primary enzymes responsible for detoxifying cellular ROS ( Muñoz-Megías et al., 2023 ). Finally, we have reported that although the echinocandins caspofungin and micafungin elicit robust ROS induction in N. glabratus , we detected no concomitant increases in lipid peroxidation or induction of oxidative genes ( Garcia-Rubio et al., 2021 ).…”
Section: Chemical Nature Of Antifungal Drug-induced Rosmentioning
confidence: 99%
See 1 more Smart Citation